Reviews. - Ratke, David C.; Tite, Philip L.; Heille, Gregory; Elias, Jacob W.; Jagessar, Michael N.; Hepokoski, Carol; Esterline, David; Stivers, Laura (Teaching Theology & Religion, 2005)
Books reviewed: L. Dee Fink. Creating Significant Learning Experiences: An Integrated Approach to Designing College Courses. Reviewed by David C. Ratke Lenoir-Rhyne College Peter Jarvis, John Holford, and Colin Griffin. The Theory & Practice of Learning. Reviewed by Philip L. Tite McGill University, Montreal, Canada Katie Geneva Cannon. Teaching Preaching: Isaac Rufus Clark and Black Sacred Rhetoric. Reviewed by Gregory Heille, O.P. Aquinas Institute of Theology Heather Fry, Steve Ketteridge, and Stephanie Marshall. A Handbook for Teaching & Learning in Higher Education: Enhancing Academic Practice. Reviewed by Jacob W. Elias Associated Mennonite Biblical Seminary William M. Timpson, Silvia Sara Canetto, Evelinn Borrayo, and Raymond Yang. Teaching Diversity: Challenges and Complexities, Identities and Integrity. Reviewed by Michael N. Jagessar Queen's Foundation for Ecumenical Theological Education UK Bonnie TuSmith and Maureen T. Reddy. Race in the College Classroom: Pedagogy and Politics. Reviewed by Carol Hepokoski Meadville Lombard Theological School Annie Howell and Frank Tuitt. Race and Higher Education: Rethinking Pedagogy in Diverse College Classrooms. Reviewed by David Esterline McCormick Theological Seminary Julie Kailin. Antiracist Education: From Theory to Practice. Reviewed by Laura Stivers Pfeiffer University